Social Ethical Values in Blended Learning for Students - Minan, Ahmad Minan Zuhri (Medina-te : Jurnal Studi Islam, 2024)
The rapid development of science and technology brings a new atmosphere to learning activities on campus. Indirectly, it turns out to erode the social ethical values of students participating in blended learning activities, so improvements are needed in every aspect of the activities as a form of normalizing a new style of contemporary learning while still paying attention to social ethical values in education. This research aims to explain the importance of internalizing social ethics values in blended learning for Department of Aqidah and Islamic Philosophy, State Islamic University Salatiga students. This research uses qualitative methods with a field study approach through interviews and observations. The object of this research is Islamic Philosophy Aqidah Department of Aqidah and Islamic Philosophy, State Islamic University Salatiga students from the 2020-2022 cohort. Research results show that first, in the category of general knowledge about social ethics, students can master general knowledge about social ethics well; second, in the category of IT proficiency, students can master and operate IT well; third, in the category of implementing or practicing social ethics in learning, students have not been able to consistently carry it out, thus consistent efforts are needed to integrate knowledge and the practice of social ethics so that synergy is well established. These efforts can be carried out through discussions and workshops on social ethics in blended learning activities, and can also be achieved by creating a community that encourages the implementation of social ethics in blended learning.